Tafsir Al-Qur’an dan Tradisi Sunda: Studi Pemikiran Moh. E. Hasyim dalam Tafsir Ayat Suci dalam Renungan - Irwan Evarial (IAIN Surakarta, 2017)
This article aims to examine the religious response of Moh. E. Hasim against the Sundanese religious tradition that is reflected in his Qur'anic commentary. Based on an analysis of the facts and views related to the religious thought of Moh. E. Hasim in his Ayat Suci dalam Renungan, this article finds that the monotheism of the Muslims of West Java, according to Moh. E. Hasim, besides worshiping Allah, they also worship idols and so forth. For that, Moh. E. Hasim forbids Muslims especially the West Java Muslim community for pilgrimage to the graves of the saints, because in reality many of the pilgrims have wrong intentions and goals. Religious ritual ceremonies such as nadran, for Moh. E. Hasim, very prohibited, because in the implementation of ritual ceremonies such as this nadran there are elements of shirk. In addition, in responding to religious traditions such as the nujuh bulanan, Moh. E. Hasim also forbids it, because it is seen that in the monthly ceremony there are elements of heresy, which include the mantras into verses of the Qur'an.